The deserts of the Southwest - Ruth, Maria Mudd. (New York : Benchmark Books, 1999)
Examines the deserts of the Southwest, their ecosystems, and their responses to temperature and weather.
Includes bibliographical references (p. - ) and index.
Keywords: Deserts -- Southwest, New -- Juvenile literature; Deserts -- Southwest, New; Desert ecology; Ecology